Evaluating the Effectiveness of the Annual Physical Training Plan for Masters +45 Women Half Marathon Athletes: A Guideline Model for Good Practices for Programming Effort Volume and Intensity - Baba Daniela; Mijaica Raluca; Nechita Florentina; Balint Lorand (Sports - MDPI, 2024)
This study presents the implementation and results of the Annual Physical Training Program for Masters +45 Half Marathoners (PASm-12), focused on optimizing athletic performance through rigorous planning of training volume and intensity. PASm-12, structured over 12 mesocycles and 52 microcycles, was applied to 6 female runners with over 10 years of experience. The results indicate that the total running volume achieved (2347 km) was 90.2% of the volume proposed by PASm-12 (2603.2 km), with statistically significant differences in most mesocycles (Cohen’s f2 = 6.24, t = −5.997, p = 0.002, indicating a large effect size). The training intensity was achieved at an average of 94.8% of what was proposed by PASm-12, with significant differences in several mesocycles (Cohen’s f2 = 0.45, t = −1.972 to −3.984, p < 0.05, indicating a moderate to large effect size). The female runners’ performances in field tests generally showed faster times than the maximum and average values proposed in PASm-12, with the exception of the final competition, where performance was slightly lower due to external competitive factors (Cohen’s d = −0.53, t = −1.192, p = 0.3). This plan, demonstrating good practice, could serve as a guideline model for amateur runners who do not have specialist counseling. PASm-12 can reduce the risk of injury, prevent excessive fatigue, and support ongoing participation in sports activities. Additionally, the implementation of this plan could provide amateur runners with a safe and effective training structure, contributing to improved health and athletic performance.
Keywords: annual physical training program; half marathon; master +45; women; training volume planning; training intensity; athletic performance